Combining in situ tribometry and triboscopy to understand third body behavior of a Cd coating. (15th February 2017) - Behera, P; Sriraman, K R; Chromik, R R; Yue, S
Abstract: The dynamic nature of third bodies and the buried nature of a sliding contact makes it difficult to interpret and correlate changes in the coefficient of friction to instantaneous materials changes. That is, full utilization of the 'tribological circuit' as proposed by Berthier, to describe tribological flows is often limited in practice unless specialized techniques are used. In this paper, an in situ tribometer is used to understand the evolution and flow of third bodies and their effect on the coefficient of friction. The in situ tribometer consisting of a transparent sapphire countersphere coupled with optical microscope is used to study the interface during linearly reciprocating sliding with simultaneous measurement of the coefficient of friction by measuring the tangential force with a time-resolved piezo sensor at a sampling rate of 800 Hz along the track length. This provides instantaneous coefficient of friction measurements along the localized track length, allowing one to plot 'spatial friction' maps, also known as triboscopic images. These graphs are cycle number on the x -axis and track position on the y -axis with a color coding for coefficient of friction. The in situ images of third bodies are correlated with the triboscopic images to identify third body flows and how they relate to local frictional changes. A soft coating (Cd) on hard substrate (low carbon steel) is used to study these third body phenomenon.